Stereoelectroencephalography and surgical outcome in polymicrogyria-related epilepsy: A multicentric study - Maillard, Louis Georges; Tassi, Laura; Bartolomei, Fabrice; Catenoix, Hélène; Dubeau, François; Szurhaj, William; Kahane, Philippe; Nica, Anca; Marusic, Petr; Mindruta, Ioana; Chassoux, Francine; Ramantani, Georgia (Annals of neurology, 2017)
OBJECTIVE: We aimed to (1) assess the concordance between various polymicrogyria (PMG) types and the associated epileptogenic zone (EZ), as defined by stereoelectroencephalography (SEEG), and (2) determine the postsurgical seizure outcome in PMG-related drug-resistant epilepsy. METHODS: We retrospectively analyzed 58 cases: 49 had SEEG and 39 corticectomy or hemispherotomy. RESULTS: Mean age at SEEG or surgery was 28.3 years (range, 2-50). PMG was bilateral in 9 (16%) patients and unilateral in 49, including 17 (29%) unilobar, 12 (21%) multilobar, 15 (26%) perisylvian, and only 5 (9%) hemispheric. Twenty-eight (48%) patients additionally had schizencephaly, heterotopia, or focal cortical dysplasia. The SEEG-determined EZ was fully concordant with the PMG in only 8 (16%) cases, partially concordant in 74%, and discordant in 10%. The EZ included remote cortical areas in 21 (43%) cases and was primarily localized in those in 5 (10%), all related to the mesial temporal structures. All but 1 PMG patient with corticectomy or hemispherotomy had a unilateral PMG. At last follow-up (mean, 4.6 years; range, 1-16), 28 (72%) patients remained seizure free. Shorter epilepsy duration to surgery was an independent predictor of seizure freedom. INTERPRETATION: PMG-related drug-resistant epilepsy warrants a comprehensive presurgical evaluation, including SEEG investigations in most cases, given that the EZ may only partially overlap with the PMG or include solely remote cortical areas. Seizure freedom is feasible in a large proportion of patients. PMG extent should not deter from exploring the possibility of epilepsy surgery. Our data support the early consideration of epilepsy surgery in this patient group. Ann Neurol 2017;82:781-794.
Keywords: dospělí; Female; dítě; předškolní dítě; Adult; výsledek terapie; ženské pohlaví; mladý dospělý; Adolescent; lidé; Treatment Outcome; mozek; polymikrogyrie; Polymicrogyria; retrospektivní studie; Drug Resistant Epilepsy; Male; Brain; refrakterní epilepsie; Child, Preschool; Young Adult; lidé středního věku; Child; mužské pohlaví; elektroencefalografie; Retrospective Studies; Middle Aged; mladiství; Electroencephalography; Humans